Greek myths - Morley, Jacqueline; Caselli, Giovanni, 1939- (New York : P. Bedrick Books, 1998)
An illustrated collection of twenty Greek myths including "Prometheus and Pandora," "Theseus and the Minotaur," "Meleager and the blazing logs," and "The story of Phaeton."
Includes index.
Keywords: Mythology, Greek -- Juvenile literature; Mythology, Greek